Capital Inflows in the Baltic Countries, Russia, and Other Countries of the Former Soviet Union : Monetary and Prudential Issues - Ize, Alain (IMF Working Papers; Working Paper ;, 1996)
Significant capital inflows were observed during the first half of 1995 in a number of FSU countries. This paper reviews the recent experience of those countries with significant inflows, examines policy responses in view of the current macroeconomic and institutional environment, discusses the use of monetary and prudential instruments to sterilize or discourage inflows, and reviews operational considerations for conducting sterilization operations.